2017
DOI: 10.1051/0004-6361/201628423
|View full text |Cite
|
Sign up to set email alerts
|

Chemical distribution of H II regions towards the Galactic anticentre

Abstract: Context. The study of the radial variations of metallicity across the Galactic disc is a powerful method for understanding the history of star formation and chemical evolution of the Milky Way. Although several studies about gradients have been performed so far, the knowledge of the Galactic antincentre is still poor. Aims. This work aims to determine accurately the physical and chemical properties of a sample of H ii regions located at R G >11 kpc and to study the radial distribution of abundances in the oute… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(90 citation statements)
references
References 77 publications
(124 reference statements)
6
83
0
1
Order By: Relevance
“…The derived gradients range from about −0.05 dex kpc −1 for H ii regions and Cepheids to about 0 dex kpc −1 for old stellar populations. Our H ii region oxygen gradient is consistent with those found using Cepheids (e.g., −0.0529 ± 0.0083 dex kpc −1 from Korotin et al 2014), other H ii region samples (e.g., −0.0525 ± 0.0189 dex kpc −1 from Fernández-Martín et al 2017), and the Mollá et al (2019a) binned H ii region sample (−0.048 ± 0.005 dex kpc −1 ).…”
Section: Discussionsupporting
confidence: 90%
“…The derived gradients range from about −0.05 dex kpc −1 for H ii regions and Cepheids to about 0 dex kpc −1 for old stellar populations. Our H ii region oxygen gradient is consistent with those found using Cepheids (e.g., −0.0529 ± 0.0083 dex kpc −1 from Korotin et al 2014), other H ii region samples (e.g., −0.0525 ± 0.0189 dex kpc −1 from Fernández-Martín et al 2017), and the Mollá et al (2019a) binned H ii region sample (−0.048 ± 0.005 dex kpc −1 ).…”
Section: Discussionsupporting
confidence: 90%
“…Another debated question is if the radial gradient maintains the same slope for all observed radial range or if it flattens (or steepens) in the outer disc. The radial gradient in MWG might be compatible with a same slope across the disc until R ≤ 18 kpc (Fernández-Martín et al, 2017;Esteban et al, 2017). However, for the CALIFA and MUSE surveys, some authors (Sánchez et al, 2014; find a flattening beyond R > 2−−2.5 R eff .…”
Section: Comparison Of Modelsmentioning
confidence: 94%
“…Combining these data with a similar survey made with the NRAO 140 Foot telescope, they get a radial gradient of −0.0446 ± 0.0049 dex kpc −1 for a larger sample of 133 nebulae. 3 Fernández-Martín et al (2017) have done observations with the William Herschel Telescope in the Los Muchachos Observatory (La Palma) for 9 Hii regions. They joined them to other literature data, and reanalysed all in a homogeneous manner.…”
Section: Nebular Data: Hii Datamentioning
confidence: 99%
“…Using optical, infrared, or radio data, different authors revealed the negative O/H abundance gradients from -0.04 to -0.07 dex kpc −1 for HII regions at Galactocentric distances of R G =0-22 kpc (Hawley 1978;Shaver et al 1983;Afferbach et al 1995;Deharveng et al 2000;Esteban et al 2005;Rudolph et al 2006;Balser et al 2015;Fernández-Martín et al 2017;Esteban et al 2017). In particular, the radial abundance gradients of the outer Galaxy have been emphasized.…”
Section: Introductionmentioning
confidence: 99%